Identification and characterization of novel associations in the CASP8/ALS2CR12 region on chromosome 2 with breast cancer risk - Lin, Wei-Yu; Marmé, Frederik; Surowy, Harald; Burwinkel, Barbara; Brenner, Hermann; Dieffenbach, Aida Karina; Arndt, Volker; Chang-Claude, Jenny; Rudolph, Anja; Hamann, Ute (Human molecular genetics, 2015)
Previous studies have suggested that polymorphisms in CASP8 on chromosome 2 are associated with breast cancer risk. To clarify the role of CASP8 in breast cancer susceptibility, we carried out dense genotyping of this region in the Breast Cancer Association Consortium (BCAC).
Advance access published on August 28, 2014
Gesehen am 24.06.2020